Phenomenological Study on the Experience of Male Nurses in Caring for Female Patients - Anik Maryunani; Rr. Tutik Sri Hariyati; Enie Novieastari (Faculty of Nursing Universitas Indonesia, 2021)
Nurses provide care equally and do not discriminate between men and women. However, male nurses face challenges and obstacles, especially when they take care of female patients. This study aimed to explore the experiences of male nurses who look after female patients by using a descriptive qualitative design with a phenomenological approach. Ten male nurse participants aged 26–43 years and having an experience of caring for female patients for at least 2 years were included in this study. Seven themes were identified: the discomfort of female patients and male nurses; patient’s trust and privacy; the identification of factors affected by body image, age, and types of sensitive areas and actions; attention to the religion, personal beliefs, ethics, and culture of patients; professionalism, role, and competencies of nurses; communication strategies and asking for female nurses for assistance based on team methods; and the view of males in the nursing profession. This study focused on two of the main themes: attention to the religion, personal beliefs, ethics, and cultures of patients and communication strategies and asking female nurses on the team for help. Results suggest that nursing facilities need to improve their patient-focused services by considering a patient’s ethical and cultural concerns, using communication strategies, and seeking team assistance when needed in accordance with a hospital’s national accreditation standards. Abstrak Studi Fenomenologi Pengalaman Perawat Laki-Laki dalam Merawat Pasien Perempuan. Perawat memberikan asuhan yang setara dan tidak membeda-bedakan antara laki-laki dan perempuan. Namun perawat laki-laki menghadapi tantangan dan kendala, terutama saat merawat pasien perempuan. Penelitian ini bertujuan untuk mengetahui pengalaman perawat laki-laki yang merawat pasien perempuan dengan menggunakan desain deskriptif kualitatif dengan pendekatan fenomenologi. Sepuluh peserta perawat laki-laki berusia 26–43 tahun dan memiliki pengalaman merawat pasien perempuan setidaknya selama 2 tahun dilibatkan dalam penelitian ini. Tujuh tema diidentifikasi, yaitu ketidaknyamanan pasien wanita dan perawat pria; kepercayaan dan privasi pasien; identifikasi faktor yang dipengaruhi oleh citra tubuh, usia, dan jenis area dan tindakan sensitif; perhatian pada agama, keyakinan pribadi, etika, dan budaya pasien; profesionalisme, peran, dan kompetensi perawat; strategi komunikasi dan meminta bantuan perawat wanita berdasarkan metode tim; dan pandangan laki-laki dalam profesi perawat. Studi ini berfokus pada dua tema utama, yaitu perhatian pada agama, keyakinan pribadi, etika, dan budaya pasien serta strategi komunikasi dan meminta bantuan perawat wanita dalam tim. Hasil menunjukkan bahwa fasilitas keperawatan perlu meningkatkan layanan yang berfokus pada pasien dengan mempertimbangkan masalah etika dan budaya pasien, menggunakan strategi komunikasi, dan mencari bantuan tim bila diperlukan sesuai dengan standar akreditasi nasional rumah sakit. Kata kunci: budaya pasien, etika, pasien perempuan, perawat laki-laki, perawatan